Acoustic Detail But Not Predictability of Task-Irrelevant Speech Disrupts Working Memory - Wöstmann, Malte; Obleser, Jonas (Frontiers in Human Neuroscience, 2016)
Attended speech is comprehended better not only if more acoustic detail is available, but also if it is semantically highly predictable. But can more acoustic detail or higher predictability turn into disadvantages and distract a listener if the speech signal is to be ignored? Also, does the degree of distraction increase for older listeners who typically show a decline in attentional control ability? Adopting the irrelevant-speech paradigm, we tested whether younger (age 23–33 years) and older (60–78 years) listeners’ working memory for the serial order of spoken digits would be disrupted by the presentation of task-irrelevant speech varying in its acoustic detail (using noise-vocoding) and its semantic predictability (of sentence endings). More acoustic detail, but not higher predictability, of task-irrelevant speech aggravated memory interference. This pattern of results did not differ between younger and older listeners, despite generally lower performance in older listeners. Our findings suggest that the focus of attention determines how acoustics and predictability affect the processing of speech: First, as more acoustic detail is known to enhance speech comprehension and memory for speech, we here demonstrate that more acoustic detail of ignored speech enhances the degree of distraction. Second, while higher predictability of attended speech is known to also enhance speech comprehension under acoustically adverse conditions, higher predictability of ignored speech is unable to exert any distracting effect upon working memory performance in younger or older listeners. These findings suggest that features that make attended speech easier to comprehend do not necessarily enhance distraction by ignored speech.